CONVERGENCE OF PERFORMANCE MEASUREMENT SYSTEM AND BALANCED SCORECARD BASED PERSPECTIVE SYSTEM TO MANAGERIAL PERFORMANCE WITH MOTIVATION AS MODERATED VARIABLES - Aslim, Ivena Christy Gunawan; Hartono, Jessica Maria (Universitas Brawijaya, Indonesia, 2019)
The purpose of this study is to know how the performance and performance of companies based on BSC on managerial performance as a moderation variable. Respondents of this research are employees and managers at PT Bank Danamon Indonesia, Tbk Surabaya Branch. Fifty four respondents participated in the survey. The type of data is primary data research. A data analysis method used in this research use analysis of moderated regression (MRA) with a program of IBM SPSS 20. Method of collecting data using questioner and sampling technique which is total method sampling. Data analysis techniques use multiple linear regression. The results of this study have theoretical and practical implications that can be used for the results of previous research and provide a new understanding of information systems and performance based on BSC on managerial performance. More details, the results of this study is useful as input for companies in the application of BSC to create a good performance measurement system. Employees will be motivated in work and will affect rewards that will also motivate employees in work. The results of this study show: (1) BSC performance measurement system has no significant effect on managerial performance improvement, (2) BSC based reward system has no significant effect on managerial performance improvement, (3) Motivation not able to moderate BSC based performance measurement system to increase managerial performance, (4) Motivation is unable to moderate BSC based reward system on improving managerial performance.